Efektivitas Metode Bernyanyi terhadap Peningkatan Minat dan Hasil Belajar Siswa pada Pembelajaran Bahasa Arab di Min 6 Sinar Rejeki Jati Agung Lampung Selatan - Lindiani Lindiani; Sri Wahyuningsih; Latifatul Khoiriyah (Journal on Education, 2024)
Students have difficulty learning Arabic so student interest and learning outcomes are still very low. Identification of the problem in this research is that in learning Arabic for class IV B, the students have followed the lessons well and in an orderly manner and done their assignments well, but there are still students who do not understand and their learning outcomes are still low and there are still many who are less active and don't like it. Arabic lessons. The aim of this research is to find out whether there is an influence of the singing method on the interests and learning outcomes of class IV B students and whether there are differences in the interests and learning outcomes of class IV B students. This type of research is quantitative with a One Group Pretest-Posttest Design (single group design). with pretest and posttest). The instruments used in this research were questionnaires, multiple choice cognitive tests, and observations. The data analysis technique used in this research is the swimmer test which includes normality tests, homogeneity tests and hypothesis tests. The results of statistical analysis show that the average value of students' learning interest in learning Arabic on the pretest questions is 59.38 and the posttest is 86.25. Meanwhile, the average score for student learning outcomes in learning Arabic for pretest questions was 61.88 and posttest was 89.38. Furthermore, based on the results of the t-test for students' interest in learning which shows that t count (15.752) > t table (2.042), it can be concluded that H0 1 is rejected and Ha 1 is accepted. while the learning results show that tcount (11,000) > t table (2,042). This shows that student learning outcomes H0 2 are rejected and Ha 2 is accepted. So it can be concluded that there are influences and differences in singing methods on increasing student interest and learning outcomes in Arabic language learning class IV B MIN 6 Sinar Rejeki Jati Agung South Lampung Academic Year 2023/2024.